Letter from Clarence Morfit to James Curtis Booth, September 28, 1854 - Morfit, Clarence (1854)
Clarence Morfit, Assistant Melter and Refiner at the New York Assay Office, discusses the ongoing progress of construction at the New York Assay Office and includes a list of items ordered.
Keywords: United States Mint; Mint of the United States; Booth, James Curtis, 1810-1888; United States. Assay Office, New York City